PENGARUH TINGKAT SUKU BUNGA, KURS DAN INFLASI TERHADAP JAKARTA ISLAMIC INDEX (JII) - SIGIT SANJAYA; NILA PRATIWI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to analyze: 1) the influence of interest rate on Jakarta Islamic Index (JII), 2) the influence of exchange rate on Jakarta Islamic Index (JII), 3) the influence of inflation on Jakarta Islamic Index (JII). This research includes causative descriptive research. The population in this research is companies listed in Jakarta Islamic Index (JII). Determination of number of sample by using total sampling. Data source is secondary data. Data were collected by browsing financial statement and data analysis using EVIEWS 8.0. Determined of number sampling by total sampling. The result of this study indicate: 1) the interest rate have significant effect on Jakarta Islamic Index (JII), 2) the exchange rate have significant effect on Jakarta Islamic Index 3) the inflation have significant effect on Jakarta Islamic Index.